Relationship between lithuanian and polish. Research for consolidation - Anušauskas, Arvydas (Genocidas ir rezistencija, 2004)
In the 20th century, Lithuanian–Polish historical relations were severely challenged. The common struggle for freedom in the uprisings of the 19th century was replaced by mutual controversies. After regaining their freedom, the two nations renounced their claims towards each other and concluded a Treaty on Friendly Relations and Good Neighbourly Cooperation in 1994. This raised new challenges for historians of both countries: whether to try to find the commonalities, mutual understanding and consensus that would bring us closer, or whether to reopen old historical wounds again.
Keywords: Lithuania; Poland; resistance